Understanding Ambiguity Attitudes - Ellsberg Choices Among Indian Students - Aggarwal, Divya (Prabandhan: Indian Journal of Management, 2018)
Individuals have often displayed a preference for known risk over unknown prospects (Ellsberg, 1961). Different variants of Ellsberg paradox have been widely used by academicians to examine the phenomena of ambiguity aversion among diverse subjects. This study examined ambiguity attitudes through a survey based approach, among a set of Indian students by using a quantitative measurement of ambiguity attitude developed by Dimmock, Kouwenberg, and Wakker (2016). Supporting the ambiguity attitude results of developed markets, a majority of the students exhibited an aversion to ambiguity and risk. The relation between risk and ambiguity attitude is inconclusive and yet to be explored further. Empirical results showed certain demographic variables to be significant in explaining ambiguity attitudes in contrast to results from developed markets. These results can be due to cultural differences, which offer a promising area for future studies. Future studies can explore the impact of family responsibility and commitments on attitudes towards ambiguity. Testing factors determining ambiguity attitude can broaden understanding of ambiguity aversion and how it can be addressed in Asian countries like India, which are collectivist in nature. Role of family commitment and marital responsibilities can elicit ambiguity attitudes different from those of developed countries. Alternatively, the study proposed to explore ambiguity attitude in relation with financial decision making with a more representative sample of investors.